DETEKSI MOLEKULER DAN ANALISIS GENETIK BEGOMOVIRUS PADA TANAMAN CABAI DI DESA PEMATANG DONOK - Ewa Aulia; Mimi Sutrawati; Tunjung Pamekas (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[MOLECULAR DETECTION AND GENETIC ANALYSIS OF BEGOMOVIRUS ON CHILLI IN PEMATANG DONOK VILLAGE]. Many symptoms of yellow curly leaf disease, but there have been no reports of viral species infected the chili plants.   The research was aimed  to determine the disease incidence of yellow leafcurl disease and detection of Begomovirus infected chilli plants in Kepahiang regency based on  polymerase chain reaction (PCR). Sampling was done by purposive sampling method based on the symptoms; yellow leafcurl, leaf malformation, and stunting. Virus detection with PCR method using general primer Begomovirus (SPG 1/2). The PCR product was sent to First Base, Malaysia for DNA sequencing. Sequencing data were analyzed using MEGA 6 (Molecular Evolutionary Genetics Analysis) software for phylogenetic tree construction. Based on field observations, the incidence of disease ranged from 96.4%-100% and the whitefly vector insect (Bemisia tabaci) was found. PCR using general primers Begomovirus obtained DNA bands measuring 912 bp according to the primary target. Based on the Blastn results, the nucleotide sequences of three Begomovirus samples from Pematang Donok Village had nucleotide similarities with the Pepper yellow leaf curl Indonesia virus (PYLCIV) isolates from Bali and Java contained in the GenBank database, with a nucleotide similarity value of 91.77%-98.99%.